2012
DOI: 10.1111/j.1744-313x.2012.01125.x
|View full text |Cite
|
Sign up to set email alerts
|

Association between a promoter polymorphism (rs2192752, –1028A/C) of interleukin 1 receptor, type I (IL1R1) and location of papillary thyroid carcinoma in a Korean population

Abstract: The interleukin 1 receptor, type I (IL1R1) is important in the pathogenesis of cancer. We investigated whether single nucleotide polymorphisms (SNPs) of IL1R1 contribute to the development of papillary thyroid carcinoma (PTC), in addition to the clinicopathological features such as the size, number, location, extrathyroidal invasion and metastasis of PTC. Three promoter SNPs (rs949963 -615G/A, rs2192752 -1028A/C and rs3917225 -1099A/G) in IL1R1 were genotyped using direct sequencing in 118 patients with PTC an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
9
0
1

Year Published

2013
2013
2020
2020

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(12 citation statements)
references
References 28 publications
2
9
0
1
Order By: Relevance
“…Although the significance of rs3917225 is decreased after adjustment for age and gender, the results of this variant could not be fully ignored as a result of its potential effect on thyroid cancer susceptibility in the Chinese Han population. Furthermore, research on a Korean cohort suggested that there was no existing relationship between rs3917225 and the location of PTC, whereas another promoter SNP, rs2192752, harbored a potential role in PTC location and development . Our results corroborate that the substitution occurring on rs3917225 (A to G) might alter the risk of thyroid cancer to a certain degree.…”
Section: Discussionsupporting
confidence: 79%
See 2 more Smart Citations
“…Although the significance of rs3917225 is decreased after adjustment for age and gender, the results of this variant could not be fully ignored as a result of its potential effect on thyroid cancer susceptibility in the Chinese Han population. Furthermore, research on a Korean cohort suggested that there was no existing relationship between rs3917225 and the location of PTC, whereas another promoter SNP, rs2192752, harbored a potential role in PTC location and development . Our results corroborate that the substitution occurring on rs3917225 (A to G) might alter the risk of thyroid cancer to a certain degree.…”
Section: Discussionsupporting
confidence: 79%
“…In this process, two identified receptors, IL1R1 and IL1R2, act as signal receivers that function distinctly and lead to different reaction results, whereas less is known with respect to their genetic variations in relation to thyroid cancer. A previous study focused on the promoter SNPs of IL1R1 and concluded that SNP rs2192752 might be associated with the risk of PTC . Considering the involvement of IL activities in various diseases, we have carried out a series of investigations of different genes and cancers and, in the present study, we evaluated the correlations between the IL1R1 and IL1R2 polymorphisms and thyroid tumorigenesis.…”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation
“…Nakki et al 32 showed that the A allele is associated with severe hand osteoarthritis. Park et al 33 polymorphism did not associated with papillary thyroid carcinoma. One of the most investigated polymorphisms in the IL1R1 gene is the SNP rs2234650:C.T (also known as 1970 C/ T PstI).…”
Section: Discussionmentioning
confidence: 99%
“…Alterations in serum concentrations of IL1b have been suggested to differentiate PTCs from atrophic thyroiditis (Kammoun-Krichen et al 2012). The inheritance of the polymorphism rs2192752 in IL1 receptor (IL1R1) increases the risk of PTC, indicating an association of this IL with DTC (Park et al 2012).…”
Section: Transforming Growth Factor Bmentioning
confidence: 99%